Counterhegemonic Narratives of Innovation: Political Discourse Analysis of Iberoamerican Countries - Bagattolli, Carolina; Brandão, Tiago (NOvation — Critical Studies of Innovation, 2019)
From the 1970s onwards, changes in economic theory began to draw attention to the relationship between economic growth and technological innovation. Technological innovation has come to be considered fundamental to boosting international trade, increasing productivity and generating more and better jobs, among other benefits. However, more recent academic narratives began to change through considering the importance of technological innovation for social purposes such as social inclusion and sustainable development. This recovered the concept of social innovation and alongside the development of a plethora of alternative innovation concepts – such as sustainable innovation, open innovation, responsible innovation, green innovation, among other “x-innovation” concepts (Gaglio et al. 2017). Nevertheless, little is known about the extent to which these counterhegemonic concepts emerge and feature in Science, Technology, and Innovation (STI) policy discourses. In this sense, this article aims to understand the use of “x-innovation” concepts and the role attributed to innovation for (allegedly) counterhegemonic purposes in the STI national policies of Iberoamerican countries within the framework of disclosing the specificity of this discourse.